Applying authentic assessment in elementary science practicum: A literature review - Martatiyana, Diana Rossa; Madani, Faisal (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2024)
Authentic assessment plays a critical role in evaluating students’ knowledge, skills, and attitudes through tasks that reflect real-life situations. In elementary science learning, practicum activities provide meaningful opportunities for students to develop scientific understanding and hands-on skills, making authentic assessment particularly relevant. This study aims to examine how authentic assessment is applied in science practicum activities in elementary schools and how it contributes to improving learning quality and students’ practical abilities. Using a literature review method, this study analyzes findings from national and international scientific articles related to authentic assessment, science learning, and practicum-based evaluation. The review reveals that authentic assessment—conducted through performance tasks, observation, rubrics, portfolios, and project-based evaluations—offers a holistic measure of students’ cognitive, affective, and psychomotor competencies. Its implementation in science practicum enhances students’ scientific process skills, critical thinking, collaboration, and conceptual understanding. Furthermore, authentic assessment provides teachers with detailed diagnostic information to develop targeted feedback and appropriate instructional decisions. Overall, the integration of authentic assessment in science practicum activities strengthens the learning process and supports the development of students’ scientific skills in meaningful and contextual ways.